Polymorphisms in p53 and the p53 pathway: roles in cancer susceptibility and response to treatment - Hrstka, Roman; Coates, Philip J; Vojtesek, Borivoj (Journal of cellular and molecular medicine, 2009)
The p53 tumour suppressor protein lies at the crossroads of multiple cellular response pathways that control the fate of the cell in response to endogenous or exogenous stresses and inactivation of the p53 tumour suppressor signalling pathway is seen in most human cancers. Such aberrant p53 activity may be caused by mutations in the TP53 gene sequence producing truncated or inactive mutant proteins, or by aberrant production of other proteins that regulate p53 activity, such as gene amplification and overexpression of MDM2 or viral proteins that inhibit or degrade p53. Recent studies have also suggested that inherited genetic polymorphisms in the p53 pathway influence tumour formation, progression and/or response to therapy. In some cases, these variants are clearly associated with clinico-pathological variables or prognosis of cancer, whereas in other cases the evidence is less conclusive. Here, we review the evidence that common polymorphisms in various aspects of p53 biology have important consequences for overall tumour susceptibility, clinico-pathology and prognosis. We also suggest reasons for some of the reported discrepancies in the effects of common polymorphisms on tumourigenesis, which relate to the complexity of effects on tumour formation in combination with other oncogenic changes and other polymorphisms. It is likely that future studies of combinations of polymorphisms in the p53 pathway will be useful for predicting tumour susceptibility in the human population and may serve as predictive biomarkers of tumour response to standard therapies.
Keywords: mutace; Neoplasms; nádory; Animals; Tumor Suppressor Protein p53; Humans; exony; lidé; zvířata; nádorový supresorový protein p53; Polymorphism, Genetic; Exons; Mutation; genetická predispozice k nemoci; Amino Acid Sequence; polymorfismus genetický; Genetic Predisposition to Disease; sekvence aminokyselin